Determination of the implementation of financial reports based on SAK EMKM - Ningdiyah, Endra Wahyu; Yulianto, Mochamad Rizal; Biduri, Sarwenda; Prasojo, Bayu Hari; Pratiwi, Rossy (Universitas Muhammadiyah Malang, 2024)
Purpose: This research aims to find Determination of the implementation of financial reports based on SAK EMKM. Methodology: The sample in this study was 65 Food and Beverage MSMEs in Sidoarjo District using convenience sampling techniques. Tech The data analysis used is analysis multiple linear regression with SPSS 27. Findings: Based on t test results show that perception MSME actors have no influence to implementation of financial reports based on SAK EMKM, meanwhile socialization of SAK EMKM and levels education owner influential to implementation of financial reports based on SAK EMKM. Practical implications: The practical implications of this research can be used as a reference in planning and implementing SAK EMKM in MSMEs. MSME players should train their skills in the field of financial accounting, as well as provide supporting facilities to help implement SAK EMKM. Regulators who experience problems in planning and implementing SAK EMKM for MSMEs can consider factors such as performance expectations, expectations of the business world, and supporting facilities. Originality/value: This research initiates the use of additional indicators from previous research as additional measuring tools in measuring readiness to implement SAK EMKM. This makes the assessment of MSME readiness in implementing SAK EMKM more comprehensive.